Вольові якості у структурі особистості та проблема виховання у вищій школі - Шамлян, Каріна (Видавництво Львівської політехніки, 2012)
Высшие учебные заведения играют ключевую роль в воспитании национального сознания, интеллектуальной элиты общества. Указывается на актуальность морально-волевого воспитания в высшей школе. Анализируется роль волевых качеств в структуре личности современных студентов, представления студентов о качествах личности “идеального” преподавателя. Higher education institutions play a key role in the education of national consciousness, the intellectual elite of a society. The author indicates the relevance of moral and volitional education in higher school. The article analyzed the role of volitional qualities in the personality structure of modern student and their understanding of the “ideal” teacher’s personality traits.
Волевые качества в структуре личности и проблема воспитания в высшей школе
Volitional qualities in the structure of a personality and the problem of education in higher school
Keywords: структура личности; волевые качества; морально-волевое воспитание; студент; преподаватель; personality structure; volitional qualities; moral and volitional education; student; teacher